Regional research in copper - Arango Sánchez, Carolina (Base Diseño e Innovación, 2015)
The Advanced Polymer Research Center (CIPA) is located in the Bío-Bío region. From there its researchers are working, among other things, on developing materials with copper to prevent the proliferation of bacteria.